Caracterização física e mineralógica de argilas do Pólo Cerâmico de Moju no Estado do Pará - NASCIMENTO, Gabriella da Silva (2023)
Ceramic materials play an essential role in various industrial and everyday applications. In this context, the analysis conducted in this study focuses on a specific category of ceramic materials known as 'red ceramics' or 'traditional ceramics.' These materials are produced in a region where the ceramic industry is developing, in the municipality of Moju, located in the state of Pará. Throughout this study, the methodological approach encompassed both laboratory experiments and field research. Qualitative methodologies and literature review were applied to enhance the understanding of the conducted analyses. The objective of this research is to provide an analysis of the local ceramic landscape, with a particular emphasis on the relationship between the clay matrices used and the formulation of new 'blends.' To achieve this purpose, analyses were conducted on the mineral compositions of the clays used, their technological properties, and their physical characteristics. Subsequently, the implications resulting from the formulation of two 'blends' developed with these raw materials were investigated. Standardized tests, following the ABNT/NBR standards and guidelines from recognized authors in the field, were employed to characterize the technological properties. Furthermore, it was observed that the proposed 'blend' exhibits notable characteristics, indicating significant potential and pointing towards a promising scenario.